Epigenetic Alteration and its Association With Downregulated FOXP3 Gene in Indian Breast Cancer Patients - Sadaf,; Akhter, Naseem; Alharbi, Raed A.; Sindi, Abdulmajeed A. A.; Najm, Mohammad Zeeshan; Alhumaydhi, Fahad A.; Khan, Mohammad Aasif; Deo, S.V.S; Husain, Syed Akhtar (Frontiers in Genetics, 2021)
Background/Aim: FOXP3 gene, known to be a potential tumour suppressor, has been identified to interact with HER2 in mammary cancer. Moreover, high expression of FOXP3 serves as a good predictor of patient's survival in breast cancer, prostate cancer, and gastric cancer. The expression and epigenetic alterations were evaluated in female Breast cancer patients. Material and Methods: The expression studies at mRNA level and protein level were conducted in 140 breast cancer cases by Real-time PCR and Immunohistochemistry (IHC), respectively. The epigenetic studies were also conducted by analyzing methylation status at the gene's promoter region using MS-PCR. Results: FOXP3 mRNA expression and protein expression were downregulated in breast cancer patients. The absence of FOXP3 protein expression is significantly associated with promoter methylation, where 70 methylated cases exhibited protein loss (70/95, 73.6%). Statistically, we also found a significant correlation between FOXP3 protein expression and TNM stage, promoter methylation, and Histological grade. Also, the methylated FOXP3 cases that did not express protein were significantly associated with positive lymph node metastasis and HER-2 status. Conclusions: The expression profile of FOXP3 may serve as a prognostic factor. Shortly, FOXP3 may stand in the most crucial list of biomarkers for breast cancer, bringing compelling results in terms of treatment and management of the disease.